Effects of high-temperature zones of coal in large silos. Issue 12 (18th June 2017) - Zhang, Jiangshi; Yan, Mingwei; Wang, Shuai; Xu, Peihui
ABSTRACT: Coal in large silos of Huanghua Port is prone to oxidation and warming during storage, which can result in fire, explosion, or domino events. Targeted monitoring to determine whether the coal reaches these high temperatures is of crucial importance. Experiments and simulation were conducted with coal species in a silo, obtaining relevant characteristics of coal oxidation under different conditions. The high-temperature coal was located approximately 7.3–22.1 m from the lower edge of the outlet. The range became wider and the position was closer to the top with the greater air-leakage speed, smaller coal-storage volume, and larger porosity, and the effect of the air-leakage speed was significant. Results were found to be credible through field observation data.